Cannabis sativa L. Extract Increases COX-1, COX-2 and TNF-α in the Hippocampus of Rats with Neuropathic Pain - Joanna Bartkowiak-Wieczorek; Małgorzata Jamka; Radosław Kujawski; Marcin Hołysz; Agnieszka Bienert; Kamila Czora-Poczwardowska; Michał Szulc; Przemysław Mikołajczak; Anna Bogacz; Anna-Maria Wizner; Karolina Wielgus; Ryszard Słomski; et al. (Molecules)
Inflammation is the critical component of neuropathic pain; therefore, this study aimed to assess the potential anti-inflammatory effects of Cannabis sativa L. extracts in a vincristine-induced model of neuropathic pain. The effects of different doses (5.0–40.0 mg/kg) of two Cannabis sativa L. extracts (B and D) on COX-1, COX-2, TNF-α, and NF-κB mRNA and protein levels were examined in the rat hippocampus, cerebral cortex, and blood lymphocytes. There were statistically significant differences in COX-1, COX-2, and TNF-α mRNA and protein expression in the hippocampus and cerebral cortex, with significant differences in COX-2 and TNF-α in the lymphocytes. Extract D dose-dependently increased COX-1 mRNA and protein in the hippocampus and cortex. In contrast, Extract B dose-dependently increased COX-1 mRNA and decreased COX-2 mRNA (in a dose of 7.5 mg/kg) and TNF-α protein levels in the cortex. Cannabis sativa L. extracts significantly influenced the expression of inflammatory genes and proteins, with effects varying based on dose and tissue type. The increased expression of COX-1, COX-2, and TNF-α (in comparison to groups receiving NaCl, vincristine, and gabapentin) in the rat hippocampus and COX-1 in the cerebral cortex suggests that Cannabis may have a pro-inflammatory effect. Due to species specificity, the results of our research based on rats require confirmation in humans. However, Cannabis sativa should be recommended with caution for treating pain with an inflammatory component.